The Holy Spirit in Mission : prophetic speech and action in Christian witness - Tyra, Gary, 1955- (Downers Grove, Ill. : IVP Academic, 2011)
Theologian Gary Tyra powerfully forges a biblical theology of the church and the Spirit. When life in the Spirit is united with the missional vocation of the church, we are empowered with hope and faith to bring the gospel to light in every context in which we find ourselves.
"Would God that all the Lord's people were prophets": the biblical connection between the coming of the Spirit and prophetic activity -- "You shall receive power": the connection between prophetic activity and missional faithfulness -- "The Spirit bade me go": missional faithfulness and the growth of global Pentecostalism -- "Men of Athens!": becoming more missionally faithful in the West -- "A man named Ananias came to see me": encouraging missional faithfulness among the evangelical rank and file.
Includes bibliographical references and indexes.
Keywords: Holy Spirit; Missions; Prophecy -- Christianity